Fenótipo neuropsicológico de adolescentes com síndrome de Down - Freire, Rosália Carmen de Lima (2013)
This research aimed to contribute to the characterization of a neuropsychological phenotype of adolescents with Down Syndrome (DS). A multicases study of six adolescents (three males and three females, aged 13 to 14 years) diagnosed with DS and treated at two institutions in the city of Natal (Brazil), was conducted. Participants were assessed using the methodological approach developed by Luria, which is composed by four complementary stages. The first one aimed to investigate the qualitative impact of DS in school life and social development of the adolescents; dimensions of behavior and social-affective aspects of the members of the study were investigated. In the second stage participants performed a battery of neuropsychological tests in order to identify strengths and weaknesses in their cognitive functioning. The third stage was incorporated into the second in order to analyze the quality of the activity of the participants along the quantitative evaluation, highlighting strategies used, errors produced among other indicators. Lastly, the fourth stage refers to the intervention with the participants. Although this is not a specific objective of the study, it is argued that the outcome of this research will subsidize the practice of different professionals working with this clinical group. The results of the first stage emphasized the presence of difficulties in social relationships and in school life of observed adolescents. In turn, the second and third stages pointed out to the presence of difficulties in tasks involving logical and abstract thinking, as well as difficulties in expressive language. In relation to visual memory, we observed a better performance in activities of lower complexity, ie, with less interference of executive functioning, particularly in terms of the functions of planning and initiative. Finally, it was found motor and mental retardation, affecting significantly the performance related to different cognitive areas. The results highlighted here can be considered as subsidies for future interventions, suggesting the need for developping projects that take into account different aspects constituents of the human subject, involving not only the individual with developmental changes, as well as their families, teachers, schools and society in general